2021
DOI: 10.1186/s12888-021-03378-w
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, emotional reactions and needs of adolescent psychiatric inpatients during the COVID-19 pandemic: a qualitative analysis of in-depth interviews

Abstract: Background The new coronavirus pandemic (COVID-19) has been accompanied by severe psychological pressure on the entire population. However, little is known about how this pandemic could affect the more vulnerable population with severe mental illness. Aims To explore adolescent psychiatric inpatients’ perceptions, emotional reactions and needs during the first wave of the COVID-19 pandemic. Methods Ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Regarding the identification of feelings experienced during hospitalization , 71.9% (n = 23) of the articles indicated that the patients and family members experienced difficult moments 47 during the hospitalization period, with feelings of loneliness 16 , 17 , 21 , 31 and isolation 16 , 17 , 21 , 29 , 31 , 40 , 41 due to the restrictions regarding visits and companions and a lack of contact between professionals and patients. 20 Feelings such as sadness, 23 , 26 , 46 fear, 17 , 18 , 20 , 22 , 24 29 , 32 , 33 , 46 anxiety, 17 , 22 , 28 , 38 , 41 , 46 worry, 17 , 20 24 , 32 , 33 , 46 nervousness, 22 guilt, 26 , 46 anger, 23 , 26 tiredness, 24 hopelessness, 46 frustration, 43 discrimination, 18 , 22 vulnerability, 29 , 32 , 46 and uncertainty 22 were also reported, associated with lack of knowledge about the disease and with the situation in which they found themselves. It is noted that the articles described concerns about the personal 21 or family 20 socioeconomic situation as aggravating factors, because of uncertainty of the economic and housing situation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the identification of feelings experienced during hospitalization , 71.9% (n = 23) of the articles indicated that the patients and family members experienced difficult moments 47 during the hospitalization period, with feelings of loneliness 16 , 17 , 21 , 31 and isolation 16 , 17 , 21 , 29 , 31 , 40 , 41 due to the restrictions regarding visits and companions and a lack of contact between professionals and patients. 20 Feelings such as sadness, 23 , 26 , 46 fear, 17 , 18 , 20 , 22 , 24 29 , 32 , 33 , 46 anxiety, 17 , 22 , 28 , 38 , 41 , 46 worry, 17 , 20 24 , 32 , 33 , 46 nervousness, 22 guilt, 26 , 46 anger, 23 , 26 tiredness, 24 hopelessness, 46 frustration, 43 discrimination, 18 , 22 vulnerability, 29 , 32 , 46 and uncertainty 22 were also reported, associated with lack of knowledge about the disease and with the situation in which they found themselves. It is noted that the articles described concerns about the personal 21 or family 20 socioeconomic situation as aggravating factors, because of uncertainty of the economic and housing situation.…”
Section: Resultsmentioning
confidence: 99%
“…Voice and video calls were described as a way of relieving the stress felt by absence of the family, 17 , 33 as well as reducing anxiety and isolation. 23 , 24 However, it was also reported that feelings such as uncertainty and sadness remained, even with the communication strategies. 46 The use of online games, 18 virtual reality, 36 telephone, 24 and television 29 was associated with the feeling of escape from reality, increasing comfort through contact with an environment other than the hospital.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, lockdown restricts individuals to stay at home strictly, and those quarantined report a rise in suicide compared to others [66]. Individuals also feel isolated from the outside world [16], reported feeling trapped in their house, and expressed concerns about the prolonged pandemic [67].…”
Section: Empirical Criterionmentioning
confidence: 99%
“…While studies relating to psychosocial effects of the pandemic on children and adolescents are prolific and continually increasing (see Chawla et al, 2021 ; Meherali et al, 2021 ), there are still notable knowledge gaps. Many studies are limited to needs of a specific group, often those with particular morbidities or life-situations (see Giannakopoulos et al, 2021 ; Mirlashari et al, 2021 ; Sharma et al, 2020 ; Tse et al, 2021 ). In addition, only a minority of studies are based on data generated directly by children or adolescents, with most instead relying on proxy reports from teachers, parents and other sources ( Berasategi Sancho et al, 2021 ; Evans et al, 2020 ; Ferrari et al, 2021 ; Ferraro et al, 2021 ; Fitzpatrick et al, 2020 ).…”
Section: Introduction and Aimmentioning
confidence: 99%